Punishment as a Price to Pay - Ch'ng Kean Siang (Contemporary Economics, 2012)
Management meted out punishment to enforce rules and encourage adherence. However, the effectiveness depended on how the employees perceive and interpret the policy. Therefore, it was uncertain how to best achieve the target. The paper tested employees' behavioral responses in two conditions, 1) when employees had to pay fines to employer and 2) when employees had to pay fines to co-workers. Condition one was a typical deterrence policy implemented to punish misconduct in an organization, and condition two tested the behavioral responses to distributive outcomes. Questionnaire was distributed to these employees to investigate perception. The experimental results indicated that employees responded differently to the two conditions, misconduct was significantly reduced in condition two but not in condition one. While employees agreed that the implementation was fair in the two conditions, they did not agree on the punishment outcomes in condition two. The employees perceived paying fines to employer was more acceptable than paying fines to co-workers. Accounting for social norms in the implementation was more successful than formal deterrence.
Keywords: C93; D03; J33; L23; 330; punishment; deterrence; lateness; field experiment; decision